Burden of Osteoarthritis in Iran: A National and Subnational Perspective, 1990−2019 Global Burden of Disease Study - Mohammad Amin Khadembashiri; Mohamad Mehdi Khadembashiri; Mohammad Saeid Khonji; Mohammad Ahmadi; Niloofar Mirdamadi; Tannaz Ahadi; Gholamreza Raissi; Masumeh Bagherzadeh Cham; Hosna Soleymanzadeh; Hamid Ansari; Bijan Forogh (Health Science Reports)
ABSTRACT Background and Aims Osteoarthritis (OA) is a chronic degenerative joint disease caused by pro‐inflammatory factors and protease activity, leading to progressive joint destruction. The data on a global scale indicate a substantial rise in OA. This study evaluates the burden of OA in Iran, given its high impact and the limited number of epidemiological studies on the condition. Methods The data pertaining to the prevalence, years lived with disability (YLD), and incidence and age‐standardized rates of OA in Iran and its subnational regions were retrieved using the Global Burden of Disease Study (GBD) Results Tool. Results Age‐standardized prevalence rate (ASPR) of OA in Iran was 5224.14 (4699.54–5821.43) and 5588.22 (5041.17–6228.61) in 1990 and 2019, which was lower than the global level. The knee was the most prevalent OA in both 1990 and 2019 in Iran, 3326.63 (2862.19–3841.62) and 3660.61 (3151.81–4228.27) respectively, followed by hand OA (1432.43 (1078.03–1922.21) in 1990 and 1476.24 (1107.91–1979.80) in 2019) and hip OA (239.08 (184.05–300.68) in 1990 and 277.65 (213.24–351.43) in 2019). The age‐standardized YLD rate of OA in Iran was 180.96 (91.76–355.00) in 1990 and 195.27 (98.67–381.01) in 2019. The age‐standardized YLD rate of site‐specific OA followed the same trend as ASPR. Tehran province, followed by Alborz and Yazd provinces, had the highest ASPR of OA in 1990. In 2019, Tehran province (6144.94 (5526.53–6862.14)) remained at the first rank, followed by Mazandaran (5536.591 (4974.13–6165.62)) and Alborz (5512.88 (4946.79–6138.54)) provinces. Our findings show that the OA incidence rate peaked in the 55–59 age group in both males and females in 1990 and 2019. Conclusion Despite being lower than global averages, the prevalence, incidence, and YLD due to OA in Iran have significantly increased over the past three decades. This highlights the need for healthcare policymakers to implement comprehensive strategies to manage OA burden and costs.